Development E-Module Flipbook-Based in Basic Programming Subjects in Vocational High School: Pengembangan E-Modul Berbasis Flipbook Pada Mata Pelajaran Pemrograman Dasar di SMK - Muhammad Surya Abadi Abd Hakam; Rahmania Sri Untari (Academia Open, 2021)
The use of learning media flipbook as learning material for students is a solution to better understand the material when the learning process takes place. This study aims to determine the development and feasibility of a-based E-Modul flipbook in basic programming subjects at SMK YAPALIS Krian. This type of research is Research and Development (R&D) using the development model Analysis, Design, Development, Implementation, Evaluation (ADDIE). The feasibility test was carried out by material experts and media experts and the results of the students' responses, the results of the validity of this study obtained a percentage of 95% with the "Very Eligible" category for the media and 95% with the "Very Eligible" category for the material, and a percentage of 84% with “Very Eligible” category for student responses. Based on these results we can conclude that E module based flipbook on the subjects of basic programming is very suitable as an alternative of learning media in SMK YAPALIS Krian.